2019
DOI: 10.1136/annrheumdis-2018-214656
|View full text |Cite
|
Sign up to set email alerts
|

mTOR inhibition by metformin impacts monosodium urate crystal–induced inflammation and cell death in gout: a prelude to a new add-on therapy?

Abstract: ObjectiveGout is the most common inflammatory arthritis worldwide, and patients experience a heavy burden of cardiovascular and metabolic diseases. The inflammation is caused by the deposition of monosodium urate (MSU) crystals in tissues, especially in the joints, triggering immune cells to mount an inflammatory reaction. Recently, it was shown that MSU crystals can induce mechanistic target of rapamycin (mTOR) signalling in monocytes encountering these crystals in vitro. The mTOR pathway is strongly implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 41 publications
3
35
1
9
Order By: Relevance
“…Although mTOR activity was enhanced, pro‐IL‐1β protein synthesis was selectively regulated by p38 MAPK signaling and not on mTOR . However, another report showed that gout patients exhibit higher expression of genes involved in mTOR pathway and lower expression of PTEN, an mTOR inhibitor, compared to healthy controls . The group showed that MSU crystals induce mTOR pathway gene expression in monocytes from healthy donors, and this was also reflected at protein level, as well as induction of IL‐1β.…”
Section: Urate‐induced Immune Programmingsupporting
confidence: 80%
See 3 more Smart Citations
“…Although mTOR activity was enhanced, pro‐IL‐1β protein synthesis was selectively regulated by p38 MAPK signaling and not on mTOR . However, another report showed that gout patients exhibit higher expression of genes involved in mTOR pathway and lower expression of PTEN, an mTOR inhibitor, compared to healthy controls . The group showed that MSU crystals induce mTOR pathway gene expression in monocytes from healthy donors, and this was also reflected at protein level, as well as induction of IL‐1β.…”
Section: Urate‐induced Immune Programmingsupporting
confidence: 80%
“…The effects of MSU crystals were reversed upon induction of autophagy and mTOR inhibition by metformin or rapamycin, which reduced cell death and lowered inflammasome activation and inflammation. In line with these data, in a retrospective cohort analysis, patients who received metformin as comedication were shown to have less frequent gout attacks and patients who were treated with colchicine expressed lower levels of mTOR activation . Metformin exerts its anti‐inflammatory effects by activating AMPK (5′ adenosine monophosphate‐activated protein kinase) which is a negative regulator of NF‐κB via the PI3K (phosphoinositide 3‐kinase)–Akt1 pathway .…”
Section: Urate‐induced Immune Programmingsupporting
confidence: 80%
See 2 more Smart Citations
“…Current drug used to treat GA may have some side effects which could be seen obviously from our previous study, such as stomach injury by indomethacin. It is urgent to identify new drugs to treat GA since it was detrimental to the health of the patients and especially in the condition of comorbidities [6]. Mitogen-activated protein kinases (MAPKs) play an important role during the pathogenesis of GA [7].…”
Section: Introductionmentioning
confidence: 99%